If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4ab + -2b + -2a = 0 Reorder the terms: -2a + 4ab + -2b = 0 Solving -2a + 4ab + -2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. -2a + 4ab + -2b + 2b = 0 + 2b Combine like terms: -2b + 2b = 0 -2a + 4ab + 0 = 0 + 2b -2a + 4ab = 0 + 2b Remove the zero: -2a + 4ab = 2b Combine like terms: 2b + -2b = 0 -2a + 4ab + -2b = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-1a + 2ab + -1b) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1a + 2ab + -1b)' equal to zero and attempt to solve: Simplifying -1a + 2ab + -1b = 0 Solving -1a + 2ab + -1b = 0 Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. -1a + 2ab + -1b + b = 0 + b Combine like terms: -1b + b = 0 -1a + 2ab + 0 = 0 + b -1a + 2ab = 0 + b Remove the zero: -1a + 2ab = b The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (132x)7-14x=0 | | 7x-2(x-5)=5(x+1)+8 | | 5x-9=5x+30-39 | | x-7=11/2 | | 7x-7x=25 | | x=20xy | | (x+7)*(x+3)= | | y=31292e(-0.2x) | | y=31292e-(9) | | (x+7)-(x+3)= | | 180=(180-(2x+60))+(3x+10)+x | | y=31292e-(0.2x) | | 180=(-180+(2x+60))+(3x+10)+x | | (x+7)+(x+3)= | | 180=(-180+2x+60)+(3x+10)+x | | 180=2x+3x+-180+60+10 | | 5(x-2)+4(x+2)=14-4x | | 4+-9x=9x+-2 | | 6=3sqrt | | 8x=-4x+-3x | | -16(t^2+4t+5)=0 | | d=1/16*8^2 | | d=1/16*7^2 | | d=1/16*9^2 | | d=1/16*60^2 | | d=1/16*20^2 | | 180=78+y+1.5y | | -1(4+x)=14 | | 7(x-2)+2(x+1)=1-3x | | 11x-2y=18 | | (12x+3x+2)-(12x+5)=6x+11 | | 2(3*5)=6y |